ФОРМУВАННЯ МУЗИЧНОГО МИСЛЕННЯ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ НА ЗАНЯТТЯХ З ОСНОВНОГО МУЗИЧНОГО ІНСТРУМЕНТУ (ФОРТЕПІАНО) (Педагогіка вищої та середньої школи, 2007)
The article considers stages of development of musical thinking on employment on the basic musical tool (piano), conducting principles, which underlie the forms and methods щf educational process and promote development of musical thinking of the future teacher of music.